JavaScript bible - Goodman, Danny, 1950-; Morrison, Michael, 1970-; Novitski, Paul; Rayl, Tia Gustaff (Wiley, 2010)
"A guide for power users demonstrates the basics of JavaScript while exploring control structures, functions, operators, form elements, hypertext links, Java Applets, and HTML applications."--Resumé vydavatele
Obsahuje rejstřík
Keywords: JavaScript (programovací jazyk); skriptové jazyky; WWW stránky; JavaScript; script languages; web pages; příručky; handbooks, manuals, etc